Application of the Fama French 3-Factor model to the cryptocurrency and token markets - Coelho, Diana Mara Costa (2020)
This study investigates the ability of the Fama French 3-Factor model in predicting the returns of the cryptocurrency and token markets. The dataset is comprised of 30 cryptocurrencies and 30 tokens with a timeframe starting at 13th of November 2018 and finishing on the 15 of May 2020. In accordance to the methodology stablished in the original study, this analysis creates 6 portfolios based on the market capitalization and network to value transaction ratio in order to create the size and profitability factors, being followed by the creation of the 25 portfolios based on the same characteristics to analyse the behaviour of the model across different scenarios. The results for the cryptocurrency market show low prediction power, with all of the model’s factors not being significant in the cross-sectional regression. Moreover, the results in the token market show a high correlation across the size and profitability factors which made the analysis on this segment to follow an adapted version of what was performed for the cryptocurrency market. The size and profitability factors were analysed separately, and the results show an even lower prediction power compared to cryptocurrencies.